2017
DOI: 10.1371/journal.pone.0170157
|View full text |Cite
|
Sign up to set email alerts
|

Protection Elicited by Nasal Immunization with Recombinant Pneumococcal Surface Protein A (rPspA) Adjuvanted with Whole-Cell Pertussis Vaccine (wP) against Co-Colonization of Mice with Streptococcus pneumoniae

Abstract: A promising alternative vaccine candidate to reduce the burden of pneumococcal diseases is the protein antigen PspA (Pneumococcal surface protein A). Since concomitant colonization with two or more pneumococcal strains is very common in children, we aimed to determine if immunization with PspA would be able to control co-colonization. We evaluated nasal immunization with recombinant PspA (rPspA) in a model of co-colonization with two strains expressing different PspAs. Mice were immunized intranasally with rPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…These results also show that protection elicited by the protein formulation involves both PspA-specific responses and responses due to wP. A reduction of pneumococcal colonization induced by nasal immunization with wP has already been observed by our group [18,23]. Nasal wash samples from mice inoculated only with wP showed higher IL-6 levels before challenge and an early increase in CXCL-1 one day after challenge with pneumococci [18], which probably contributed to the reduction in the bacterial load in the nasopharynx, possibly by the early recruitment of phagocytic cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results also show that protection elicited by the protein formulation involves both PspA-specific responses and responses due to wP. A reduction of pneumococcal colonization induced by nasal immunization with wP has already been observed by our group [18,23]. Nasal wash samples from mice inoculated only with wP showed higher IL-6 levels before challenge and an early increase in CXCL-1 one day after challenge with pneumococci [18], which probably contributed to the reduction in the bacterial load in the nasopharynx, possibly by the early recruitment of phagocytic cells.…”
Section: Discussionsupporting
confidence: 84%
“…wP used in this work is composed of whole-cell pertussis inactivated with 0.2% formalin and was produced by Instituto Butantan (São Paulo, Brazil). Our group has previously used wP as an efficient nasal adjuvant for immunization with PspA [18,23]. Vaccines were administered in a volume of 10 µL using a micropipette.…”
Section: Immunizationmentioning
confidence: 99%
See 1 more Smart Citation
“…https://doi.org/10.1371/journal.pone.0228055.g003 Our group has been working on the use of the adjuvant properties of wP for the formulation of PspA-based vaccines. Such combined formulations (wP plus recombinant purified PspA) have proved to be effective when inoculated through the nasal and through the subcutaneous routes in mice [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the whole cell pertussis vaccine (wP) is a potent adjuvant to PspA, able to enhance the induction of specific antibodies and protection against invasive pneumococcal infection and nasal colonization in animal models [8,9]. Besides the whole bacteria, Pertussis toxin (PT) and Filamentous hemagglutinin (FHA) can also exert adjuvant activity when combined to PspA [10] leading us to propose that combined pertussis-PspA vaccines could be interesting approaches to immunize against infections caused by both Bordetella pertussis and pneumococci.…”
Section: Introductionmentioning
confidence: 99%